BREASTFEEDING TECHNIQUES AND MOTHERS ATTITUDE IN EXCLUSIVE PRACTICE - Adiesti, Ferlia; Mufdlillah, Mufdlillah; Rosida, Luluk (Jurnal Kesehatan - STIKes Prima Nusantara, 2021)
Background: Providing optimal nutrition for babies is giving breast milk. Breastfeeding is beneficial for the health of mothers and babies in providing nutrition. Sufficient knowledge about public health pedoaman and benefits of exclusive breastfeeding that have been known to have benefits in the long term. Poor knowledge of mothers and negative attitudes towards less than optimal breastfeeding practices are the causes of poor baby health.. The researcher took the title because there was no previous research on attitudes and techniques in the success of following which was carried out in the form of a scoping review.Objective: The aim of the study was to see the techniques and attitudes of mothers in breastfeeding infants 0-6 months in increasing the coverage of exclusive breastfeeding.Method: Research using research by conducting checks that use steps, namely identifying research questions, identifying relevant research, selecting research, mapping data, compiling, summarizing, and reporting data. Determination of research questions using the PICO framework. The search for articles was carried out by including inclusion and exclusion criteria as a condition in selecting data. Researchers used 4 databases, namely Science Direct, Willley, Pubmed, and Google Scholar. The results of article selection are included in the PISMA diagram. Article used 13 of 101 articles. Articles deemed suitable for analysis for data entered in a data chart. The final stage is measuring the article.Results: The mapping of themes that can be used as a formulation of research problems consists of 2 themes, namely attitudes and techniques. The discussion of themes and sub themes is carried out based on the articles that have been selected.Conclusion: Increasing breastfeeding coverage needs to be pursued as an important intake for children aged 0-6 months, one of which influences breastfeeding techniques on mother's attitude in exclusive breastfeeding. That can be given by further researchers are the title of research with the best title in producing breast milk, increasing the reach of programs related to exclusive breastfeeding, comparing the cultural and educational influences received as a form of belief in exclusive breastfeeding, mother's perception of exclusive breastfeeding in the eyes of mothers. primiparous and multiparous.